2018
DOI: 10.1111/mcn.12660
|View full text |Cite
|
Sign up to set email alerts
|

A behaviour change intervention with lipid‐based nutrient supplements had little impact on young child feeding indicators in rural Kenya

Abstract: Poor infant and young child feeding (IYCF) practices are associated with linear growth faltering. Our objective was to evaluate the impact of a nutrition and water and sanitation for health intervention on three IYCF indicators-minimum dietary diversity (MDD), minimum meal frequency (MMF), and minimum acceptable diet (MAD) in Kenyan children. Households were randomized into one of eight groups: (a) active control; (b) passive control; (c) water quality (W); (d) sanitation (S); (e) handwashing (H); (f) combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…However, in addition to supplementation, our trial included behavioral recommendations to increase dietary diversity. We found significant differences in reported dietary diversity in the 2 N groups in Bangladesh (19) but not in Kenya (15). However, even in the Bangladesh control group at the 2-y follow-up, 78% of children met the minimum dietary diversity indicator of ≥4 food groups/d, whereas 92% of children in the N and WSH+N groups met this criterion.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, in addition to supplementation, our trial included behavioral recommendations to increase dietary diversity. We found significant differences in reported dietary diversity in the 2 N groups in Bangladesh (19) but not in Kenya (15). However, even in the Bangladesh control group at the 2-y follow-up, 78% of children met the minimum dietary diversity indicator of ≥4 food groups/d, whereas 92% of children in the N and WSH+N groups met this criterion.…”
Section: Discussionmentioning
confidence: 63%
“…Adherence to LNS recommendations was high (>90%) in the N arms, but there were no differences in complementary feeding practices between groups (10, 15). Adherence to the WSH interventions varied, but was generally lower than the LNS adherence (10).…”
Section: Methodsmentioning
confidence: 89%
“…Linear growth failure is a strong marker of a complex of pathological disorders that in sum lead to increased morbidity and mortality, loss of physical growth potential, reduced neurodevelopment and cognitive functions and decreased human potential (UNICEF‐WHO‐The World Bank Group, ). Attempts to address linear growth faltering through a number of interventions including high‐energy plant‐based foods fortified with a mix of multiple micronutrients, improved water, hygiene and sanitation, behaviour change communication to improve infant and young child feeding practices have had limited effects on linear growth (Byrd et al, ; Lin et al, ; Nair et al, ; Null et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that the prevalence of achieving minimum dietary diversity, defined as consuming at least four of seven key food groups (grains or tubers, legumes or nuts, dairy products, animal flesh foods, eggs, vitamin A-rich fruits and vegetables, and other fruits and vegetables) in the past 24 hours, was higher in the nutrition group than in the control group in the WASH Benefits trial but not when nutrition interventions were combined with improved water quality, sanitation, and handwashing. 28 To test whether this difference persisted in the population of index children with ARI symptom data, we used generalized linear models (with robust standard errors and fixed effects for clusters) to compare the prevalence of achieving minimum dietary diversity in the nutrition versus WSHN group. We examined differences between the nutrition and WSHN groups in breastfeeding rates for index children for three indicators: any breastfeeding in the past 24 hours, early initiation of breastfeeding (i.e., caregiver reported putting the child to the breast immediately or within the first hour after birth), and exclusive breastfeeding for 6 months (i.e., caregiver reported exclusive breastfeeding for 6 months, corrected by the reported age of cessation and complementary foods eaten).…”
Section: Methodsmentioning
confidence: 99%